Primary cutaneous anaplastic large-cell lymphoma resembling infratemporal space infection: a case report - Xiaohan Yan; Wenhao Ren; Shaoming Li; Zhuang Zhu; Ling Gao; Keqian Zhi (BMC Oral Health, 2024)
Abstract Background Primary cutaneous anaplastic large-cell lymphoma (PC-ALCL) is a rare T-cell lymphoma belonging to the CD30 + T-cell lymphoproliferative disorders. The case of PC-ALCL in the temporal region is exceedingly rare. Herein, we report a case of PC-ALCL involving the temporal region mimicking infratemporal space infection. Case presentation A 78-year-old woman presented to maxillofacial surgery service with a 6-month history of swelling and pain in the left side of her face. Laboratory investigations found an elevated C-reactive protein (CRP). Imaging findings showed enlarged lymph nodes and extensive thickening of subcutaneous tissue of the left temples. Based on these findings, the infratemporal space infection was suspected initially. The patient underwent incision and drainage, and we unexpectedly found no pus in the lesion area. Incisional biopsy showed necrosis and extensive involvement of the left temples by a diffuse infiltrate containing large, atypical cells. The tumor cells were positive for CD30, CD3, Ki67. They were negative for ALK (SP8), CD5, CD8, CD20 and PAX5. After considering these findings, a diagnosis of PC-ALCL was rendered. The patient was admitted to the lymphoma department for systemic chemotherapy and no relapse occurred during a follow-up period of six months. Conclusions This report suggests that if there are suspicious intraoperative manifestations, carrying out a biopsy simultaneously, using Hematoxylin and eosin (HE) staining, and a comprehensive Immunohistochemistry (IHC) panel are essential to diagnosing PC-ALCL to prevent misdiagnosis.